24 hour –Pregnancy Unique Quantification of Emesis Scale Usage to Quantify Nausea and Vomiting - Qurra-tul-Ain, Rabail Gul, Shagufta Yasmin , Syeda Batool Mazhar, Sadaf Zarar (Journal of Rawalpindi Medical College, 2018)
Background: To assess disease burden of nausea and vomiting of pregnancy ( NVP) and to perform external validity of the 24 hour PUQE score by examining its ability to evaluate various characteristics associated with NVP. Methods: In this cross sectional study pregnant ladies with nausea and vomiting were included. PUQE -24 score and well-being scores were recorded. Chi square and fisher-exact test were used to assess association between PUQE score severity and qualitative variables. One-way ANOVA was used to find association between PUQE-24 score and wellbeing score. P value of <0.05 was taken as significant. Results: A total of 117 patients at mean gestational age 10.61 weeks(±2.12) presented with NVP. Mild PUQE score was seen in 54.7%, moderate in 39.9% and severe in 15.4%. PUQE -24 score had significant association with severity of NVP, need of hospitalization,ER visits,need of intravenous antiemetics and fluids and lower well-being score.(p<0.05) Conclusion:For the assessment of NVP symptoms, the PUQE- 24 seems as a reliable tool. It is simple and can help in patient management and follow up.